The London congestion charging - Santos, G (Brookings Institution Press, 2008)
Traffic congestion is a textbook example of an externality and therefore calls for some government intervention if efficiency is to be achieved. Simple as road pricing may sound, it has seldom been adopted as a real world policy. With the exception of Singapore, which in 1975 implemented the first such measure, no other examples were to be found until February 2003, when London introduced a congestion charge for the privilege of driving in the central area. Many towns and cities around the world have been observing the case with interest. Stockholm implemented its own version of road pricing in 2007, and San Francisco is currently entertaining the idea. The New York State Assembly was considering congestion pricing for New York City but rejected it in April 2008. The main reason why there are so few examples of road pricing is lack of public and therefore political acceptability, although London has proved that neither is an insurmountable obstacle to achieving the goal of reducing congestion. However, conditions in London before congestion charging took effect were very special: average speeds were extremely low, the transit use rate was unusually high, laws were already in place, and five years of technical analysis of different options for congestion charging had been completed. This paper discusses the reasons why London's government thought that charging for congestion made sense, the basic goal of the congestion charging project, and policymakers' intentions and expectations when they established it. It describes the project and how it works, exploring costs, revenues, and economic benefits, and focuses on the different impacts that congestion charging has had in London, including impacts on traffic, transit use, land use, and property prices. It also includes an assessment of the political aspects of the project, followed by an analysis of its basic goals and a theoretical assessment of the scheme as an instrument for achieving those goals. New plans to link the congestion charge to emissions also are discussed.